Cardiovascular neural regulation is impaired in amyotrophic lateral sclerosis patients. A study by spectral and complexity analysis of cardiovascular oscillations. (23rd March 2015) - Dalla Vecchia, Laura; De Maria, Beatrice; Marinou, Kalliopi; Sideri, Riccardo; Lucini, Anna; Porta, Alberto; Mora, Gabriele
Abstract: Although the clinical hallmark of amyotrophic lateral sclerosis (ALS) is a progressive motor weakness, different combinations of autonomic nervous system (ANS) dysfunction have been described. No clear correlation between ANS abnormalities and ALS clinical characteristics has been found so far. We investigated the cardiovascular neural regulation in ALS with a non-invasive methodology, using spectral and complexity analysis of heart rate variability (HRV) and systolic arterial pressure (SAP) variability. In all patients, we found low RR variance and an altered response to orthostasis, witnessed by the indices derived from both spectral and complexity analysis of HRV and SAP variability. Besides, we identified two groups with distinct autonomic profiles at rest, those with higher, and those with lower cardiac sympathetic activity. In both groups the cardiovascular response to tilting was impaired. Our study outlined that ANS is invariably impaired in ALS, and patients can present with different baseline patterns. Our findings suggest important pathophysiological, clinical and prognostic insights. The presence of different autonomic profiles at rest supports the new concept of ALS as a multisystem disorder with phenotypic heterogeneity. Our results are also relevant in clinical practice. They can help to improve patients' management, and to identify prognostic factors.